PATHOLOGY OF BONE TISSUE IN DISEASES OF THE GASTROINTESTINAL TRACT - N. K. Slohova; I. N. Totrov (Кубанский научный медицинский вестник, 2015)
This article presents the results of the study of bone tissue in patients with gastrointestinal diseases. Conducted osteodensimetric study revealed a high prevalence of lower BMD in different areas of the skeleton of these patients. Osteoporosis and osteopenia in patients met more frequently than in the control group. Also showed a significant decrease in the content of vitamin D in blood serum, in comparison with the control group. Identified some factors in the development of osteopenic syndrome in patients with gastrointestinal diseases.